2020
DOI: 10.1515/jpm-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, oral health and dental education: an overview on the northeast of Italy

Abstract: ObjectivesTo evaluate the level of knowledge of pregnant women and puerpers about oral health and prevention during and after gestation.MethodsOne hundred women aged 18–49 years (mean age 33 ± 6 years) were included in this cross-sectional study. An anonymous questionnaire with 24 items related to oral health has been administered during or just after pregnancy. Firstly, answers have been analyzed on the full population and then subdividing the sample on the base of age ranges (G1: 18–25 years, G2: 26–35 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
3
1
3
Order By: Relevance
“…The current study found much higher values, whereby 54.5% (by dentist) and 71.7% (by gynecologist) rated that they were informed, while the vast majority felt well educated on oral health during pregnancy. The international literature regarding comparable questionnaire-based examinations showed heterogeneous findings, which also indicated a somewhat worse situation than in the current study [22][23][24][25]. A multicentric study in US showed an insufficient knowledge on oral health issues in pregnant women [22].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The current study found much higher values, whereby 54.5% (by dentist) and 71.7% (by gynecologist) rated that they were informed, while the vast majority felt well educated on oral health during pregnancy. The international literature regarding comparable questionnaire-based examinations showed heterogeneous findings, which also indicated a somewhat worse situation than in the current study [22][23][24][25]. A multicentric study in US showed an insufficient knowledge on oral health issues in pregnant women [22].…”
Section: Discussioncontrasting
confidence: 51%
“…This current study has its main strength in the large sample size, which is higher than in comparable national and international studies [20][21][22][23][24][25]. Moreover, the comprehensive use of validated questionnaire-based instruments revealed some new insights into the topic.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Impaired oral hygiene due to nausea and vomiting, as well as food cravings for sugary food to offset it, further increases antenatal mother's risk of developing dental caries (Sari, Saddki & Yusoff, 2020). Besides that, oestrogen and progesterone enhance vascular permeability, and vascular proliferation could result in the recruitment of more inflammatory cells in the gingival (Costantinides et al, 2020). As a result, the inflammatory response of periodontal tissues to bacteria in dental plaque is exaggerated even to a minimal amount of plaque accumulation (Rathee & Jain, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, muitos profissionais não promovem atendimento a esse público, justificando se sentirem inseguros por não obterem conhecimento suficiente sobre o prénatal odontológico e entre diversas atribuições a este fato, destaca-se a falta de conteúdo oferecido na graduação e/ou pós-graduação 5 . Somado a isso, as crenças em mitos e tabus da cultura popular que desaconselham a realização de tratamentos odontológicos durante a gravidez, contribuem para que haja uma aversão ao atendimento por parte das pacientes, neste período 6,7 .…”
unclassified